The Influence of Brand Ambassador, Brand Image, Brand Awareness, Price, and Product Quality on Azarine Sunscreen Purchasing Decisions in Semarang City - Yulianto, Sabatina Wulan Dwi; Bakhtiar, M. Rifki (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the influence of brand ambassador, brand image, brand awareness, price, and product quality on purchasing decisions for Azarine Sunscreen products in Semarang City. This study employs a quantitative method with a sample size of 200 respondents, utilizing a non-probability sampling technique. Data were collected through questionnaires and analyzed using the SPSS application to test the influence of variables. The results show that the five variables —namely, brand ambassador, brand image, brand awareness, price, and product quality — are proven to be valid and reliable measurement constructs. The partial results suggest that the brand ambassador, brand image, brand awareness, and price variables have a positive and statistically significant impact on purchasing decisions. At the same time, product quality has a negative and significant influence on purchasing decisions. Moreover, simultaneously, brand ambassador, brand image, brand awareness, price, and product quality all influence purchasing decisions.